Testing staining techniques to determine age and growth of Dasyatis pastinaca (Linnaeus, 1758) captured in Iskenderun Bay, northeastern Mediterranean - Girgin, H.; Basusta, N. (Wiley, 2016)
This study tested the suitability of several staining methods to determine the age of common stingray (Dasyatis pastinaca) from Iskenderun Bay, Turkey. A total of 384 specimens (16.6 cm-69.3 cm disc width) were obtained by trawling between September 2010 and December 2011. Sex ratio of the samples was 53% males and 47% females. Appropriate age determination was firstly demonstrated using Safranin-O staining. Age readings were made by two independent readers and the index of average percent error (IAPE) determined as 6.3% for Safranin-O, 6.8% for Crystal Violet, 7.9% for Alcian Blue, and 9.3% for Silver Nitrate. Safranin-O and Crystal Violet staining methods provided the best results. Verification of temporal growth ring formation was by marginal increment analysis. Disc width-weight relationships were determined by W = 0.0272*DW3.06 for females and W = 0.0247*DW3.08 for males. Estimates of the von Bertalanffy growth parameters indicated a larger asymptotic disc width (DW infinity = 127.06 cm) for females than for males (DW infinity = 114.54 cm); growth parameters were k = 0.058 year(-1), t(o) = -1.508 and k = 0.041 year(-1), t(o) = -3.632 for females and males, respectively.
1st International Fisheries Symposium -- MAR 24-27, 2013 -- Girne, CYPRUS
Keywords: Common Stingray; Rhinobatos-Rhinobatos; Sea; Shark; Reproduction; Guitarfish; Turkey; L.